2011
DOI: 10.1007/s10800-011-0277-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical fabrication of Rh–Pd particles and electrocatalytic applications

Abstract: Electrochemical deposition method was employed for the fabrication of rhodium-palladium (Rh-Pd) particles on the glassy carbon electrode (GCE) and indium tin oxide (ITO) electrode surface. Surface morphological analysis of Rh-Pd film has been carried out using scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis. Here, the electrodeposited Rh-Pd particles were found in the average size range of 30-200 nm. The electrochemical activities of the Rh-Pd film have been investigated using cyclic vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…The nano Au-CRV film modified GCE has greater sensitivity and performed detection in lab and real drinking water samples up to 15µg/L (Rajkumar et al 2011). …”
Section: Gold Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The nano Au-CRV film modified GCE has greater sensitivity and performed detection in lab and real drinking water samples up to 15µg/L (Rajkumar et al 2011). …”
Section: Gold Electrodesmentioning
confidence: 99%
“…The success of these portable instruments will be an added advantage for the under-developed and developing countries for the monitoring and management of environmental pollution. Bare electrode 1 -------0.02 (Forsberg et al 1975) Microelectrode 0.5 Mineral, sea and tap water 0.025 (Salaün et al 2007) Au-CRV e film-GCE ---300-3000 Mineral, tap and spring water 15 (Rajkumar et al 2011) Au-NPs f SPE g ---0-250 Canal water 0.4 (Khairy et al 2010) Au-NPs-GCE ---1.5-225 Real water samples 0.07 (Gu et al 2013) Au-NPs-GCE ---0.1-12 Ground, lake and drinking water 0.047 (Huang and Chen 2013) 3D Au nanodendrite ---0.1-70 ------ (Huan et al 2011) a Au = gold, b GCE = glassy carbon electrode, c Ibu-AuNSs = ibuprofen gold nanostructure, d NEE = nano electrode ensemble, e CRV = crystal violet, f NPs = nanoparticles, g SPE = screen printed electrode, 2000) a IIP = ion imprinted polymers, b NPs = nanoparticles, c Au = gold, d TZT-HDTA-clay = 2-thiazoline-2-thiol-hexaecyltrimethylammonium clay, e MWCNTs = multiwalled carbon nanotubes, f N-BDMP = nitro benzoyl diphenyl methylenphosphorane, Highlights  Spectroscopic methods for the determination of Hg(II) and As(III) in low concentrations are costly.  Electrochemical methods provide better sensitivities and relatively easy to use.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Most recently, we reported the TiO 2 -Gr nanocomposite prepared by hydrothermal method using graphene as templates to immobilized TiO 2 nanoparticles. PT modified electrodes have been reported and have shown good electrochemical performance [27,28]. Taurine is a well-known dissociated amino acid, which exhibits important physiological functions and pharmacological characteristics.…”
mentioning
confidence: 99%
“…104 Our group has recently developed a facile and effective electrochemical Cr(VI) sensor using Au NPs-decorated TiO 2 NTs. 105 Rajkumar et al 106 demonstrated an electrochemical sensor for arsenic in controlled laboratory and drinking water samples using a nano Au-crystal violet lm, which was fabricated on a glassy carbon electrode. 5A shows the SEM images of Au NPs decorated TiO 2 NTs.…”
Section: Detection Of Heavy Metalsmentioning
confidence: 99%